Microbial Electrolysis for Hydrogen Generation - Balo, Figen; Sua, Lutfu S. (wiley, 2025)
The majority of the generation of H 2 so far results from water electrolysis and the combustion of petroleum-based energy sources. H 2 generation from microbial electrolysis cells is a viable option for renewable energy. Bioelectrochemically aided microbial reactor, also called microbial electrolysis cell, is an inventive, renewable, and environmentally clean sector for H 2 generation. Through different bacteria strains, microbial electrolysis cells generate H 2 primarily from waste biomass. The H 2 synthesis from various substrates utilizing microbial electrolysis cells, often referred to as electrofermentation or biocatalyzed electrolysis cells, has recently attracted considerable research interest. In a microbial electrolysis cell, organic material is broken down into CO 2, protons, and electrons by electrochemically active microorganisms that are growing on the anode's surface. H 2 is generated at the cathode when protons and electrons join after passing through the exterior electricity circuit and the electrolyte, respectively. This paper starts with a comprehensive overview of microbial electrolysis cells. Next, it goes into detailed information related to the design of microbial electrolysis cell generation. Then, the most effective substrate is determined among the diverse substrates used in microbial electrolysis cells according to important properties for H 2 generation by employing an AHP analysis. © 2025 Scrivener Publishing LLC. All rights reserved.
Keywords: AHP analysis; H2 generation; Microbial electrolysis cells; Renewable energy; Substrates